PERAN ASEAN DALAM MEMBERANTAS TINDAK PIDANA TERORISME DI KAWASAN ASIA TENGGARA BERDASARKAN CONVENTION ON COUNTER TERRORISM - Diana Dewi Setia Wati; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
South East Asia Regions are one of most region that have big potency. To keep harmonization in this region ASEAN has a rules to keep saffety in South East Asia Regions. But untill now the growwth of transnational crime especially terorism be a important issues because Indonesia, Malaysia, Singapore and Filiphina. So needed coordination between all of countries in South East Asia Region to counter on terorism.The problem of this research are how rule of ASEAN to counter on terorism in South East Asia Region based on Convetion of ASEAN on Counter Terorism and what the obstructed of ASEAN to counter on terorism in South East Asia Region based on Convetion of ASEAN on Counter Terorism.This reasearch use decriptions methodes or normative of law research, source of data from 3 data that: primer data, secunder data and tertier data, and technic collecting data with interview and library research after collect data then analize by qualitative to answer the research problem with deduktif analize.This research have a result that of ASEAN to counter on terorism in South East Asia Region based on Convetion of ASEAN on Counter Terorism are with make a dealing with the ASEAN Countries. Some of agreements are Asean regional Forum, Conference of Ministrial Meeting, ASEANAPOL, ASEAN Counter on Terorism with European Union and ASEAN + 3. In order the obstructed of ASEAN to counter on terorism in South East Asia Region are ASEAN principall that non interventions, ASEAN still focus in social and culture issues, conflict of politic domestic in ASEAN countries like Thailand, Myanmar and conflict between the state in ASEAN Region like Indonesia and Malaysia about the borderless cause.Keywords :Counter on Terorism – ASEAN – Rule